Incidence of the autoimmune dermatosis in dogs and cats and retrospective study of 40 cases of discoid lupus erythematosus attended at the Dermatology Service of the College of Veterinary Medicine and Animal Science of UNESP - Botucatu - Palumbo, Mariana Isa Poci [UNESP]; De Araújo MacHado, Luiz Henrique [UNESP]; Conti, Jorge Piovesan; De Oliveira, Fernanda Cristina [UNESP]; Rodrigues, Jéssica Correa [UNESP] (Universidade Estadual de Londrina, 2010)
The objectives of this study were to do a survey of the autoimmune skin diseases and update the records regarding the occurrence of discoid lupus erythematosus in canine and feline populations attended at the Dermatology Service of the College of Veterinary Medicine and Animal Science of UNESP - Botucatu, including species, gender, breed, age, location and characteristic of the lesions. Results have shown that the order of occurrence, regarding the number of cases of autoimmune skin diseases in the animals attended by the Dermatology Service in the period from 1988 to 2007 was: discoid lupus erythematosus, pemphigus folliaceus, uveo-dermatologic syndrome, pemphigus vulgaris, systemic lupus erythematosus, necrolytic migratory erythema, multiforme erythema and plasmacytic pododermatitis. All the animals with discoid lupus erythematosus were dogs and most of them were mongrel females. More frequently breeds affected by discoid lupus erythematosus were german shepherd and akita and the mean age was 56 months. Most lesions were located in nasal planum, narines and periocular area and were characterized by crusting, depigmentation and erythema.
Incidência das dermatopatias auto-imunes em cães e gatos e estudo retrospectivo de 40 casos de lupus eritematoso discóide atendidos no serviço de dermatologia da Faculdade de Medicina Veterinária e Zootecnia da UNESP - Botucatu
Keywords: Autoimmune skin diseases; Cats; Discoid lupus erythematosus; Dogs